Screening Characteristics of Ultrasonography in Detection of Ankle Fractures - Shojaee, Majid; Hakimzadeh, Farhad; Mohammadi, Parisa; Sabzghabaei, Anita; Manouchehrifar, Mohammad; Arhami Dolatabadi, Ali (Archives of Academic Emergency Medicine, 2018)
Introduction: Ankle fracture is one of the most common joint fractures. X-ray and physical examination are its main methods of diagnosis. Recently, ultrasonography (US) is considered as a simple and non-invasive method of fracture diagnosis. This study evaluated the diagnostic accuracy of US in detection of ankle fracture in comparison to plain radiography. Methods: In this diagnostic accuracy study, which was done in emergency departments of Imam Hossein and Shohadaye Tajrish hospitals, Tehran, Iran, during 2014, 141 patients with suspected diagnosis of distal leg or ankle fracture were examined by US and radiography (gold standard), independently. Screening performance characteristics of US in detection of distal leg fractures were calculated using SPSS version 21. Results: 141 patients with the mean age of 34§11.52 years (range: 15–50) were evaluated (75.9% male). Radiography confirmed ankle fracture in 102 (72.3%) patients. There was a significant correlation between the results of US and radiography [Agreement: 95%; kappa: 0.88 (95% CI: 0.80–0.97); P Ç 0.001]. The screening performance characteristics of US in detection ankle fracture were as follows: sensitivity 98.9% (95% CI: 93.5% - 99.9%), specificity 86.4% (95% CI: 71.9%–94.3%), PPV 94.1% (95% CI: 87.1%–97.6%), NPV 97.4% (95% CI: 84.9%– 99.8%), PLR 16 (95% CI: 7.3–34.8), and NLR 0.02 (95% CI: 0.003 – 0.182). The area under the ROC curve of US in this regard was 95.8 (95% CI: 91.9§99.7). Conclusion: According to the results of this study, we can use US as an accurate and non-invasive method with high sensitivity and specificity in diagnosis ofmalleolus fractures. However, the inherent limitations of US such as operator dependency should be considered in this regard.